2015
DOI: 10.1038/modpathol.2015.38
|View full text |Cite
|
Sign up to set email alerts
|

An international study to increase concordance in Ki67 scoring

Abstract: Although an important biomarker in breast cancer, Ki67 lacks scoring standardization, which has limited its clinical use. Our previous study found variability when laboratories used their own scoring methods on centrally stained tissue microarray slides. In this current study, 16 laboratories from eight countries calibrated to a specific Ki67 scoring method and then scored 50 centrally MIB-1 stained tissue microarray cases. Simple instructions prescribed scoring pattern and staining thresholds for determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(156 citation statements)
references
References 23 publications
6
144
0
6
Order By: Relevance
“…In addition, in other studies IHC-detected Ki67 levels were associated with quantitatively assessed proliferation in first-generation genetic signatures [37][38][39]. Finally, different studies have reported a high interlaboratory variability in Ki67 scoring on breast tumors among some of the world's most experienced pathologists [40,41]. Clinical decision-making regarding treatment options in breast cancer often relies on the application of a Ki67 cutoff to classify patients into "Ki67 high" or "Ki67 low" risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in other studies IHC-detected Ki67 levels were associated with quantitatively assessed proliferation in first-generation genetic signatures [37][38][39]. Finally, different studies have reported a high interlaboratory variability in Ki67 scoring on breast tumors among some of the world's most experienced pathologists [40,41]. Clinical decision-making regarding treatment options in breast cancer often relies on the application of a Ki67 cutoff to classify patients into "Ki67 high" or "Ki67 low" risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…In their early multi-institutional study on Ki67 reproducibility in breast cancer, Polley et al showed that analytical validity of Ki67 LI was "unacceptably poor" [53]. Calibration using web-based tool allowed to increase concordance in reporting of Ki67 LI [61]. Despite these efforts, it is probably still too early to recommend usage of Ki67 LI for management of patients with breast cancer [53,61,62].…”
Section: Post-analytical Phase Of Ki67 LI Assessmentmentioning
confidence: 99%
“…Significant efforts were made to improve reliability of Ki67 reporting in breast cancer [39,53,61]. In their early multi-institutional study on Ki67 reproducibility in breast cancer, Polley et al showed that analytical validity of Ki67 LI was "unacceptably poor" [53].…”
Section: Post-analytical Phase Of Ki67 LI Assessmentmentioning
confidence: 99%
“…Currently, there is no standardized cutoff value for Ki-67. [54][55][56] A meta-analysis of 46 studies with 12 155 patients has shown that high Ki-67 labeling correlated with increased relapse and decreased survival. However, the threshold designated as high Ki-67 labeling ranged from 3.5% to 35%.…”
Section: Ki-67mentioning
confidence: 99%